Kings and usurpers in the Seleukid Empire : the men who would be king - Chrubasik, Boris (Oxford classical monographs, 2016)
This volume focuses on ideas of kingship and power in the Seleukid Empire, specifically the role of usurpers. Redefining the king as only one of several political players, it advances a political history predicated on social power and argues that despite its strong rulers the empire was structurally weak and the position of its kings precarious